Template-free synthesis of hierarchical MoO2 multi-shell architectures with improved lithium storage capability - Tang, Shasha (2017)
A hierarchical multi-shell structure of MoO2 is synthesized through a template-free one-pot solvothermal method. The relative MoO2 electrode exhibits high reversible specific capacity of 780 mA h g−1 after 40 cycles, good stability, high capacity retention and improved rate performance in the lithium ion battery application. This material has a unique hierarchical architecture which is a combination of pure hollow structure and core-shell structure. Such a hierarchical multi-shell structure can not only amplify active mass-electrolyte contact area and minimizes lithium ion diffusion path, but also provides a unique interstitial void space to relieve the huge volume change of material. Materials with a hierarchical multi-shell structure are expected to be promising candidates in lithium ion batteries application.